Evaluation of the Quezon City Public Library System's nonvisual desktop access service in assisting the blind and the visually impaired with the implication on its promotion and service delivery - Liwag, Marijoy G.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2015)
Since public libraries offer services to make their libraries accessible to people with disabilities particularly to the blind and the visually impaired, it is important that these services are evaluated to know if the library serves it purpose in assisting the blind/visually impaired and to further improve it. The Quezon City Public Library (QCPL) installed NonVisual Desktop Access (NVDA), a computer screen reader in 16 of their branches in 2011 but only 10 among those have maintained the NVDA service until today. The goal of this study was to evaluate the NVDA service of the QCPL for the blind and the visually impaired in order to come up with ideas on how can the QCPL improve the service.
A total of 85 respondents from 10 QCPL branches were surveyed for this study which were comprised of 49 library users, 33 librarians and staff, and three visually impaired clients. The library users were asked to answer a questionnaire about their awareness of the NVDA service. The librarians and staff answered a questionnaire that measured their knowledge in utilizing the service and the strategies they used in order to promote the service. The three visually impaired users were interviewed to know their awareness and user satisfaction in using the NVDA in the QCPL near them. All of the respondents were asked to give their suggestions on how can the QCPL improve the NVDA service in terms of promotion and service delivery.
The data gathered from the questionnaires and interviews showed that: a) 61% of the library users do not know that QCPL offers NVDA service; b) 26% of the libraries who know that QCPL offers NVDA service learned about it from the QCPL's website; c) 58% of the librarians and staff of the 10 QCPL branches do not know how to operate the NVDA; d) 43% of the librarians and staff who know how to operate NVDA were taught by a coworker; e) all of the visually impaired respondents learned about the NVDA service from a friend/relative; and f) all of the visually impaired respondents said that although the QCPL needs to improve the service, they are already grateful and satisfied that this kind of service for the blind and visually impaired exists. To improve the NVDA service in terms of promotion, the respondents suggested that QCPL can put up Barangay posters and make announcements, promote the NVDA service in public and private schools, use different social mediums, communicate with Non-Governmental Organizations (NGOs), and use the word of the mouth marketing. On the other hand, the respondents suggested that QCPL can improve the NVDA service in terms of service delivery by making the NVDA service available in all of the QCPL branches, by training their librarians and staff in operating NVDA, by purchasing additional gadgets (headphones, speakers, braille keyboards, and computers), and by installing NVDA in all of their computers.
Undergraduate thesis(B.L.I.S.)--University of the Philippines, Diliman
Keywords: Public libraries -- Philippines -- Quezon City -- Evaluation; Libraries and the blind -- Philippines -- Quezon City; Libraries and people with visual disabilities -- Philippines -- Quezon City